Key Focus Areas for Enhancing Interpersonal Leadership Practices among Teachers: Insights from Teachers and Experts - Arjun, R.S.; Bindhu, C.M. (Voices of Teachers and Teacher Educators, 2024)
Several academic fields including philosophy, psychology, and education discuss interpersonal leadership. It is also a popular concept in the scenario of self-transformation of ideas for getting desired outputs in the life of Modern Man. As times change, approaches to understanding this term are updated, and suitable relearning becomes necessary. As the world is functioning as an era of specialisations, concepts like interpersonal leadership must be transacted appropriately, fitting individuals in their respective areas of expertise. According to Covey (2013), the principles of interpersonal leadership are one of three key dimensions that an individual must be aware of in order to evolve from a state of independence to interdependence and attain public victory. Some theories consider interpersonal leadership as a single explorative idea, and some accommodate it as a part of more prominent themes or as a structure of different perceptions. Awareness about six paradigms of human interaction and five dimensions of Win/Win, namely Character, Relationships, Agreements, Supportive Systems and Processes, are connected with Interpersonal Leadership. Primary school teachers can mould the next generation by preparing with a scientifically guided attitude on interpersonal leadership practices, if they come to grasp its the importance. The present study aims to find the specific areas for enhancing interpersonal leadership practices relevant to teachers and student teachers. This investigation includes experiences, insights, suggestions from present primary school teachers and experts, and themes identified from related research documents.